The importance of service quality that influence customer satisfaction in Hotel IPM Dungun /Adrian Seling Bilong - Seling Bilong, Adrian (Faculty of Business and Management, Universiti Teknologi MARA,Terengganu, 2010)
The purpose of this research is to study about the importance of SERVQUAL dimensions (reliability, responsiveness, assurance, empathy and tangibles) that influence customer satisfaction in Hotel IPM Dungun. This research is to identify the solutions of the problem occurs that face by Hotel IPM in delivering services to their internal and external customers. The main problem faces is the failure of Hotel IPM Dungun Manager and employees to deliver excellent services to their customers during the service process. This is also because the failure of the Manager and Hotel IPM staff practicing SERVQUAL in delivering service to their customers. Regarding to this circumstances, it can affect the level of customer satisfaction towards the service deliver and the image of the Hotel IPM itself. Due to the problems, there are certain circumstances why the research objective was developed. First, is to identify the relationship between independent variable (reliability, responsiveness, assurance, empathy and tangibles) and dependent variable (customer satisfaction). Next is to identify which are the most important SERVQUAL dimensions that influence customer satisfaction that will brings profit and advantages to the Hotel IPM. Last objective is to give suggestions and recommendations to Hotel IPM Dungun to ensure customers’ satisfaction towards its service delivered. The findings of the research state that all the variables, reliability, responsiveness, assurance, empathy and tangibles have a relationship with customer satisfaction of service delivered. Overall, based on the findings, there are several recommendations that have been suggested in order to help and improve the way Hotel IPM delivered services to their customer and satisfy them.